2007
DOI: 10.2135/cropsci2007.01.0038
|View full text |Cite
|
Sign up to set email alerts
|

A Cryptic Wheat–Aegilops triuncialis Translocation with Leaf Rust Resistance Gene Lr58

Abstract: Genes transferred to crop plants from wild species are often associated with deleterious traits. Using molecular markers, we detected a cryptic introgression with a leaf rust resistance gene transferred from Aegilops triuncialis L. into common wheat (Triticum aestivum L.). One agronomically desirable rust‐resistant introgression line was selected and advanced to BC3F11 from a cross of hexaploid wheat and A. triuncialis In situ hybridization using A. triuncialis genomic DNA as a probe failed to detect the alien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 53 publications
1
55
0
1
Order By: Relevance
“…Recently, researchers have identified a few disease-resistant alien translocation lines with cytologically undetectable alien segments, which were called "cryptic alien introgressions" (Kuraparthy et al, 2007b;He et al, 2009;Luo et al, 2009). In the present study, two markers flanked YrSn0096 on the long arm of chromosome 4A, whereas GISH mapped a small alien segment to the short arm of a wheat chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have identified a few disease-resistant alien translocation lines with cytologically undetectable alien segments, which were called "cryptic alien introgressions" (Kuraparthy et al, 2007b;He et al, 2009;Luo et al, 2009). In the present study, two markers flanked YrSn0096 on the long arm of chromosome 4A, whereas GISH mapped a small alien segment to the short arm of a wheat chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Traits of interest can be transferred to the recipient crop without cytological changes in its genomic constitution [82], implying that the introgressed chromatin segments are cryptic. This type of translocation, known as cryptic translocation, cannot be detected by cytological techniques, and molecular methods must be used [83]. Although the mechanism for the occurrence of such cryptic translocations is unknown, their occurrence seems frequent [84].…”
Section: Alien Genetic Resources and The Prospect Of Wheat Fhb Resistmentioning
confidence: 99%
“…Most of these translocations, despite carrying useful alien genes, have a questionable value for wheat improvement because the large transferred chromosome segments do not adequately compensate for the wheat genes they replace or they carry additional genes conferring undesirable traits. However, in a few instances, traits of interest were transferred to recipient genotypes without inducing detectable cytological or genetic changes (Dong et al 2004;He et al 2009;Kuraparthy et al 2007;Luo et al 2009b;Multani et al 1994;Ren and Zhang 1997). The results of the SSR analysis showed that YU24 and YU25 amplified wheat-specific products evenly distributed over all chromosomal arms.…”
Section: Susceptible Reactionmentioning
confidence: 99%